Well-Being as a Higher Education Management Imperative: Mapping Psychological Dimensions of Migrant Management Students - Uhud Darmawan Natsir (International Humanity Advance, Business & Sciences, 2026)
The psychological well-being of migrant students represents a critical yet underexplored dimension of people management in higher education. As universities increasingly enroll students from diverse geographic backgrounds, understanding and strategically managing student psychological well-being has become an important institutional responsibility. This study aimed to describe the psychological well-being of migrant management students at the Department of Management, Faculty of Economics and Business, Universitas Negeri Makassar, and to examine its implications for people management in higher education. A quantitative descriptive design was employed, with respondents selected through purposive sampling. Psychological well-being was measured using Ryff’s Scale of Psychological Well-Being, which covers autonomy, environmental mastery, personal growth, positive relations with others, purpose in life, and self-acceptance. The instrument testing indicated that all items were valid, while the reliability result demonstrated acceptable internal consistency. Descriptive analysis revealed that the overall psychological well-being of migrant management students was categorized as high. Self-acceptance emerged as the strongest dimension, whereas autonomy was identified as the lowest dimension and remained within the moderate category. These findings suggest that migrant management students generally demonstrate positive psychological well-being; however, targeted managerial interventions are still needed, particularly to strengthen autonomy and self-directed decision-making. This study contributes to the development of student human capital management discourse and provides an empirical basis for designing student support programs in Indonesian higher education institutions.